2007
DOI: 10.1094/pdis-91-7-0809
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Ecology of Blackberry yellow vein associated virus

Abstract: Symptoms of leaf vein yellowing and bush decline in blackberry were attributed to infection by a novel crinivirus named Blackberry yellow vein associated virus (BYVaV). The disease is an emerging threat to blackberry production because it can cause substantial yield loss. The objective of this study was to identify the source and means of spread of BYVaV. A survey of blackberry plants for BYVaV from wild, cultivated, and nursery stocks was conducted. Insect traps and healthy blackberry sentinel plants were pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Symptoms of BYVD only occur when blackberry plants are infected with more than one virus. Symptoms include vein yellowing, oak-leaf or irregular patterns of chlorosis, ringspots, and line patterns ( Figure 3 ; Susaimuthu et al, 2007, 2008). Floricanes can also be severely affected leading to misshapen fruit and cane dieback.…”
Section: Group-1mentioning
confidence: 99%
“…Symptoms of BYVD only occur when blackberry plants are infected with more than one virus. Symptoms include vein yellowing, oak-leaf or irregular patterns of chlorosis, ringspots, and line patterns ( Figure 3 ; Susaimuthu et al, 2007, 2008). Floricanes can also be severely affected leading to misshapen fruit and cane dieback.…”
Section: Group-1mentioning
confidence: 99%
“…For this reason we used aphids and mites for BYV transmission with negative results (data not shown). BVY-infected sentinel plants were asymptomatic, and detection by RT-PCR revealed that BYVaV, the originally described agent of BYVD, was not spreading in the field (Susaimuthu et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Surveys of wild blackberry plants indicated that BVY was present in symptomatic leaf samples of some of the wild blackberry plants (Rubus fruticosus, identified by Dr. Johnnie L. Gentry, University of Arkansas, Fayetteville) from two of the 19 Arkansas counties surveyed (Susaimuthu et al, 2007). The symptomatic wild blackberry plants that tested positive for BVY were also positive for BYVaV (Susaimuthu et al, 2007), and these samples were from wild blackberry plants in northwest Arkansas where the BYVD affected production field is located.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations